Astronuts. vol. 1, The Plant Planet - Scieszka, Jon (Astronuts, 2019)
Carbon dioxide is out of control on Earth, and the fate of humankind rests in the paws of four experimental, untested Animal Astronauts (AlphaWolf, SmartHawk, LaserShark, and StinkBug) who are seeking another habitable planet; first destination is the Plant Planet which at first looks perfect, except that the abundant plant life can think for itself--and it thinks that it really does not like the AstroNuts.